Spatiotemporal Patterns and Driving Factors of Carbon Footprint in Coastal Saline Cropland Ecosystems: A Case Study of the Yellow River Delta, China - Yang Li; Dingwen Zhang; Ying Wen; Xiaoling Liu; Yi Zhang; Guangmei Wang (Land)
Coastal saline cropland ecosystems are becoming increasingly vital for food security in China, driven by the decline in arable land and the growing demand for resource-intensive diets. Although developing and utilizing saline land can boost productivity, it also impacts greenhouse gas (GHG) emissions. This study uses the Yellow River Delta as a case study to analyze the spatial-temporal patterns of carbon footprints in saline croplands from 2001 to 2020 and their correlations with climate factors, cropland management scale, and agricultural mechanization. The results reveal that agricultural production in this region is characterized by high inputs, emissions, and outputs, with carbon emission efficiency improving significantly due to a reduction in net carbon emissions. Major sources of carbon emissions include electricity, chemical nitrogen fertilizers, nitrogen input, and straw return, which together account for 65.06% of total emissions. Based on these findings, three key principles have been proposed for policy recommendations to enhance carbon emission efficiency. First, adopt tailored strategies for regions with different salinization levels. Second, strengthen cropland drainage infrastructure to mitigate the adverse effects of heavy rainfall. Third, expand the scale of cropland management through land transfers and promote agricultural mechanization. These insights offer valuable guidance for mitigating GHG emissions in coastal saline cropland ecosystems.